ANALISA KUALITAS CITRA RADIOGRAFI THORAX PROYEKSI POSTERO ANTERIOR (PA) DENGAN VARIASI FOCUS FILM DISTANCE (FFD) DI INSTALASI RADIOLOGI RUMAH SAKIT UMUM SUNDARI - TJUANDA, YUSRIWAN (LP2MTBM MAKARIOZ, 2021)
Radiology is one of the supporting installations in a hospital that is useful for diagnosing a disease. This requires inspection techniques and image quality, with the aim of knowing the comparison of radiographic image quality on Thorax examination of the PA projection with FFD variations of 120 cm, 160 cm, 180 cm at Sundari General Hospital, using the general radiographic modality of the Toshiba brand. The examination was carried out on 9 adult patients. A radiographic image is obtained with differences in contrast which is analyzed visually, to distinguish which image has higher quality in terms of density, contrast and detail values. It can be concluded that from the Thorax PA radiographic image, the 120 cm FFD is more optimal. And for the examination of PA thoracic patients in theory it is expected to use a 180 cm FFD